Counterions Control Whether Self‐Assembly Leads to Formation of Stable and Well‐Defined Unilamellar Nanotubes or Nanoribbons and Nanorods. Issue 23 (7th May 2014) - Shi, Dong; Schwall, Christian; Sfintes, George; Thyrhaug, Erling; Hammershøj, Peter; Cárdenas, Marite; Simonsen, Jens B.; Laursen, Bo W.
Abstract Self‐assembly of the amphiphilic π‐conjugated carbenium ion ATOTA‐1+ in aqueous solution selectively leads to discrete and highly stable nanotubes or nanoribbons and nanorods, depending on the nature of the counterion (Cl− vs. PF6−, respectively). The nanotubes formed by the Cl− salt illustrate an exceptional example of a structural well‐defined (29±2 nm in outer diameter) unilamellar tubular morphology featuring π‐conjugated functionality and high stability and flexibility, in aqueous solution.